Be My Guest: A Survey of Mass Communication Students' Perception of Guest Speakers. Issue 2 (3rd April 2017) - Merle, Patrick F.; Craig, Clay
ABSTRACT: The use of guest speakers as a pedagogical technique across disciplines at the college level is hardly novel. However, empirical assessment of journalism and mass communication students' perceptions of this practice has not previously been conducted. To fill this gap, this article presents results from an online survey specifically administered to such students ( N = 545) at a large public research university and a small liberal arts college. Results of statistical significance indicate that inviting a guest speaker is most valuable to students when the speaker comes from the industry and interacts face-to-face with the audience through personal examples and career tips rather than a formal slide-based lecture. Finally, this article contributes to and expands upon previous literature by offering a set of recommendations for the use of guest speakers in journalism and mass communication curriculum.